Iron concentration in exhaled breath condensate decreases in ever-smokers and COPD patients *Disclaimer: This report has been reviewed by the National Health and Environmental Effects Research Laboratory, United States Environmental Protection Agency, and approved for publication. Approval does not signify that the contents necessarily reflect the views and policies of the Agency, nor does mention of trade names or commercial products constitute endorsement or recommendations for use. (21st August 2018) - Ghio, Andrew J; Soukup, Joleen M; McGee, John; Madden, Michael C; Esther, Charles R
Abstract: Investigation employing bronchoalveolar lavage supports both increased and decreased iron concentrations in the epithelial lining fluid (ELF) of smokers. Exhaled breath condensate (EBC) is an alternative approach to sampling the ELF. We evaluated for an association between iron homeostasis and both smoking and a diagnosis of chronic obstructive pulmonary disease (COPD) by measuring metal concentrations in EBC samples from non-smoker controls, smoker controls, and individuals diagnosed with COPD. The total number of EBC specimens was 194. EBC iron and zinc concentrations (mean ± standard error) in the total study population were 0.610 ± 0.025 and 40.73 ± 1.79 ppb respectively. In linear regressions, total cigarette smoking in pack years showed a significant (negative) relationship with EBC iron concentration but not with EBC zinc concentration. Iron concentrations in EBC from GOLD stage II, III, and IV patients were all significantly decreased relative to those from non-smoker and smoker controls. In contrast to iron, zinc concentrations in EBC were not significantly different than those from non-smoker and smoker controls. It is concluded that smoking decreases EBC iron concentrations and patients diagnosed with COPD have significantly lower EBC iron concentrations. These results likely reflect an increased burden of cigarette smoke particles in the lower respiratory tract of ever-smokers and patients with COPD and the capacity of components in this particle to complex iron.